Imitação, desejo e virtude: a teoria mimética de René Girard e a ética como educação para a virtude - Fernandes, Rebeca Traldi de Vitto (2023)
The present work proposes an approximation between the mimetic theory, developed by René Girard, and ethics as virtue education. From these two core themes, the exposition was divided into four main chapters: It begins by situating the work in the current state of contemporary discussion while delimiting the presupposed conception of ethics and establishing the distinction between virtue ethics and Duty-based ethics, as well as their possible incompatibility. Then, it is dedicated to a brief presentation of Girard and his mimetic theory, pointing out to what extent it can be related to ethics. After that, we present the ethics as education towards virtue and virtue ethics is contextualized in the contemporary discussion through the work of Alasdair MacIntyre. Finally, the hypothesis of virtue as a possible counterpoint against mimetic rivalry is introduced, which permeates and expands the previous topics